VD_FINDINFO HC / 2012 / 160 vom 7. März 2012 - VD Tribunal cantonal (2012)
BAIL À LOYER, RÉSILIATION, RÉSILIATION ABUSIVE, PRINCIPE DE LA BONNE FOI, ANNULABILITÉ | 257d al. 1 CO, 257d al. 2 CO, 257d CO, 271 al. 1 CO, 271 CO